Electric machine : - Cathey, Jimmie J. (McGraw-Hill, 2001)
A unique text that integrates the popular interactive computer software MATLAB to handle the tedious calculations arising in electric machine analysis, Readers are able to quickly calculate and plot wide range performance data through the use of developed computer software for each energy conversion, Includes a reference list at the end of each chapter, and an expanded Web site will include a downloadable version of the solution manual and the MATLAB M-files.